Phonetic instruction in English language learning: Perceptions of Yemeni elementary students - Ali Salah, Fatima Lardhi; Noor Raha, Mohd Radzuan (2022)
The ultimate goal of this research is to explore the EFL students’ opinions on the teaching of English phonetics (IPA) at the elementary level. To achieve the purpose of the study, a semistructured interview was conducted. All interviews were audio recorded with the participants’ consent. The participants were 25 female students at Almina Educational Complex for Girls who were in elementary 2 (Year 8) which is their second year of studying English as the school’s main subject. The participants received a 3-week IPA instructions of English diphthong sounds. All recorded interviews were analyzed manually. Semistructured interview data revealed that students’ fear of making mistakes was the dominant reason behind their difficulties in English pronunciation. Moreover, lack of practice and the absence of pronunciation training were viewed as the main causes for the students’ mispronunciation in English language. The results of the current study provide empirical evidence to the importance of the phonetics instructions at the elementary level.